FREKUENSI KASUS GAGAL GINJAL AKUT PADA ANAK YANG DISEBABKAN OBAT-OBATAN SIRUP YANG MENGANDUNG ETILEN GLIKOL PADA TAHUN 2022 - Lutfiah, Alya; Pratiwi, Pratiwi; Suharsih, Suharsih; Khairiyah, Syifa; N, Septian Aditiya; A, Tiara Maharani; Frianto, Dedy; Arfania, Maya (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
In Indonesia, The frequency Acute Kidney Injury (AKI) in children has increase. According KEMENKES’s data until 18 October 2022 frequency Acute Kidney Injury (AKI) in children has increase and potentially caused by used of drugs syrup containing Ethylene Glycol, with deaths of child reaching up to 60% from 206 cases reports from 20 Provinces in Indonesia. Acute Kidney Injury (AKI) is inability kidneys to filtrate compounds inside the body. Generally characterized by cretainin serum has a levels increase in urine, and disability kidney on homoestatis electrolyte and nitrogen. Inside the kidneys, the ethylene glycol compound will be excreted by the enzyme and oxidized into aldehyde glycol and re-oxidated into oxalate acid compounds as a trigger for kidney stones that will damage the kidney.